An enhanced rule mining algorithm to detect suspects of crime against women in the state of Tamil Nadu - Usha, D.; Chitradevi, D. (International Journal of Engineering and Technology, 2018)
Crime against women in India has become a prominent topic of argument in the recent years and the issue has been brought to the foreground for concern due to the increasing trend in crimes performed against women. It is the major challenge to the investigators to detect and prevent crimes, particularly crime against women. Most of the crimes get reported and a massive dataset is being generated every year. Analyzing the crime reports can help the law enforcement officers to take preventive measures for reducing the crime, but processing this voluminous data is backbreaking and error prone. So, the application of various data mining techniques can help in visualizing the crime trend. Crime is one of the interesting applications where data mining plays an important role in terms of prediction and analysis in the interest of society. This paper covers in detail analysis of modus operandi of committing crimes and effective use of data mining techniques and algorithms in narrow down to identify the criminals at a short span of time.Â Â
Keywords: Crime Pattern; Data mining; Rule Mining Algorithm; Modus Operandi.